1980
DOI: 10.1021/bi00566a038
|View full text |Cite
|
Sign up to set email alerts
|

Proton nuclear magnetic resonance and electron paramagnetic resonance studies on skeletal muscle actin indicate that the metal and nucleotide binding sites are separate

Abstract: The distance separating the high-affinity binding sites of actin for a divalent metal ion and nucleotide was evaluated by using high-resolution proton NMR and EPR spectroscopy. Replacement of the Ca2+ or Mg2+ bound to the high-affinity divalent cation site of G-actin by trivalent lanthanide ions such as La3+, EU3+, or Gd3+ results in an increase in the mobility of the bound ATP as observed in the NMR spectra of G-actin monomers. Little difference was observed between the spectra obtained in the presence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…FRET measurements with the fluorescent cation Tb(III) bound to the Me site and FTP as the acceptor at the NUC site suggested that these sites were about 16~ apart (Barden & dos Remedios/1984). 1H n.m.r, data using lanthanide ions support this conclusion (Barden et al, 1980;. On the other hand, other FRET data (using e-ATP/Co(II) or Ni(II) as the donor-acceptor pair) have demonstrated that the distance between Me and NUC sites is no more than 104 (Miki & Wahl, 1985) and there are 31p n.m.r, data to support this conclusion (Brauer & Sykes, 1982).…”
Section: Cys-10mentioning
confidence: 84%
“…FRET measurements with the fluorescent cation Tb(III) bound to the Me site and FTP as the acceptor at the NUC site suggested that these sites were about 16~ apart (Barden & dos Remedios/1984). 1H n.m.r, data using lanthanide ions support this conclusion (Barden et al, 1980;. On the other hand, other FRET data (using e-ATP/Co(II) or Ni(II) as the donor-acceptor pair) have demonstrated that the distance between Me and NUC sites is no more than 104 (Miki & Wahl, 1985) and there are 31p n.m.r, data to support this conclusion (Brauer & Sykes, 1982).…”
Section: Cys-10mentioning
confidence: 84%
“…Assuming that Tb3' has the highest affinity for the M2+-binding site, they sought perturbations of aromatic residues using NMR (27) and UV spectroscopy (28); on finding none they reasoned that this portion of the primary sequence (the first 20 residues) was uniquely distant from aromatic residues. On also failing to find effects of bound Tb3+ on the ring protons of bound nucleotide, they concluded that the two sites were more than 1.6 nm distant (22); this observation too fitted the idea that the M2+-site was in the NH2-terminal residues. It should be noted that Brauer and Sykes (29) found the phosphorus nuclei of bound nucleotide to be near the M2'-binding site, but the finding may not be contradictory in as much as intranucleotide distances can be considerable.…”
mentioning
confidence: 99%
“…A proteolytic removal of residues eliminates the ability of actin to bind M2+ (4,22). The calcium-binding protein from carp, the "CBP" (23), has been investigated, and there exist homology studies (24) that have compared the amino acid sequences involved in various calcium-binding sites.…”
mentioning
confidence: 99%
“…This suggests that either the Tb3' site is located a short distance from the Co2+ site as has been claimed [49, 501 or the replacement of the bound divalent cation with a trivalent lanthanide ion may increase the separation between the two sites by about 0.5 nm. This may be achieved either by the trivalent cation mobilizing the nucleotide base [22] so that the trivalent and divalent cation sites are actually identical but the base is translocated when a trivalent cation binds. Alternatively, a conformational change in the actin may be induced which involves a widening of the cleft [5], or a combination of the two processes may apply.…”
Section: 3-diazolementioning
confidence: 99%